The Realization of Strategies of Refusal to Direct Requests by Sundanese and Minangnese Students - Aulya Hanifah Gusly (Passage, 2017)
This study seeks to examine the realization of strategies of refusal to direct requests by Sundanese and Minangnese students. This study also examines the contribution of power relation, social distance, and rank of imposition to the realization of the refusal strategies. This study employs a descriptive qualitative approach. The data used in the present study were gathered from a Discourse Completion test (DCT) that was distributed to 10 Sundanese and 10 Minangnese respondents. The data were analyzed by using Takahashi and Beebe’s (1987) classifications of refusal. The findings show that 13 (out of 16) refusal strategies of Takahashi and Beebe (1987) are evidenced in this study. It is found that from all the 13 strategies, statement of regret and excuse, reason, explanation are the two most frequently used strategies. It is also found that there is no substantial difference in terms of the strategies employed by both Sundanese and Minangnese students; however, some differences can be noted especially with regard to the use of mother tongue, in which Sundanese respondents mixed Indonesian with Sundanese more often than the Minangnese. The study also reveals that less power of the requesters, less social distance between the refusers and requesters, and lower rank of imposition tend to lead the refusers to use the excuse, reason, explanation strategy as their first choice. Meanwhile, more power of the requesters, larger social distance between the refusers and requesters, and higher rank of imposition tend to lead the refusers to use the statement of regret strategyKeywords: Refusal, Sundanese, Minangnese, power, distance, imposition